POL-INTEL - Tanja Kammersgaard Christensen (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract Since the adoption of Section 2a of the Danish Police Act in 2017, the police have been able to conduct cross-sectional information analyses in IT systems designed for this purpose, and thus process personal data for purposes other than those for which they were originally collected. This is regulated by the Executive Order on Cross-sectional Information Analyses. According to this executive order, the police shall use the POL-INTEL system to perform the analyses. The article discusses the police’s use of personal data for new purposes based on the Law Enforcement Directive, the Danish Law Enforcement Act, and relevant case law from the European Court of Justice. It assesses whether the regulation of POL-INTEL in the Executive Order on Cross-sectional Information Analyses adheres to the principles of purpose limitation, data minimisation and legality, or whether there is a need for changes to the Danish regulation .